Microsoft graphics techniques for multimedia - Crabe, Geneviéve (AP Professional, 1996)
Macintosh Graphic Techniques for Multimedia is an information packed resource that provides invaluable tools for both the beginning graphic designer and the experienced multimedia developer for creating attractive and easy to use on-screen images and graphics. It thoroughly covers the techniques for designing interactive products, including 3-D graphics, user interface design... and, of course, pages for the World Wide Web.